Temporal bisection task with dogs: an exploratory study - Domeniconi, Camila (2017)
The temporal bisection task, one of the most widely used to study time perception, has helped to understand the psychophysics of time and the mechanisms of timing across different species. We extended the temporal bisection task to dogs. Five dogs were reinforced for choosing a yellow but not a blue stimulus after a 1-s tone, and for choosing a blue but not a yellow stimulus after a 4-s tone. After they learned this conditional discrimination, the dogs chose between the blue and yellow stimuli after tones with intermediate durations (1.4, 2.0, and 2.8 s). The results showed that the proportion of “Long” choices increased monotonically with stimulus duration. Moreover, the point of subjective equality was slightly below the geometric mean of the trained tone durations. These psychophysical results are consistent with those obtained with other nonhuman species, and suggest that common mechanisms underlie timing across different mammals and birds.